2003
DOI: 10.1167/iovs.02-0492
|View full text |Cite
|
Sign up to set email alerts
|

Caspase Activation in an Experimental Model of Retinal Detachment

Abstract: The apoptotic photoreceptor cell death in experimental retinal detachments is associated with caspase activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
100
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(104 citation statements)
references
References 16 publications
3
100
1
Order By: Relevance
“…RD model was created in the left eye of the rats by subretinal injection of 10 mg/ml sodium hyaluronate (AWTMZSN, Bausch & Lomb Freda, Jinan, SD, China) as described earlier. 6,9 Briefly, the rats were anesthetized with an intraperitoneal injection of 10% chloral hydrate and their pupils were dilated with 0.5% tropicamide and 0.5% phenylephrine hydrochloride eye drop (Santen Pharmaceutical Co. Ltd, Osaka, Japan); the sclera was punctured at approximately 1.5 mm posterior to the limbus with a 30-gauge needle with special caution taken to avoid damaging the lens, the needle was slowly advanced into the vitreous cavity through the sclerotomy, and then to the subretinal space by producing a small hole in peripheral retina. Sodium hyaluronate was slowly injected until the neurosensory retina almost totally detached from the underlying retinal pigment epithelium.…”
Section: Establishment Of Retinal Detachmentmentioning
confidence: 99%
See 1 more Smart Citation
“…RD model was created in the left eye of the rats by subretinal injection of 10 mg/ml sodium hyaluronate (AWTMZSN, Bausch & Lomb Freda, Jinan, SD, China) as described earlier. 6,9 Briefly, the rats were anesthetized with an intraperitoneal injection of 10% chloral hydrate and their pupils were dilated with 0.5% tropicamide and 0.5% phenylephrine hydrochloride eye drop (Santen Pharmaceutical Co. Ltd, Osaka, Japan); the sclera was punctured at approximately 1.5 mm posterior to the limbus with a 30-gauge needle with special caution taken to avoid damaging the lens, the needle was slowly advanced into the vitreous cavity through the sclerotomy, and then to the subretinal space by producing a small hole in peripheral retina. Sodium hyaluronate was slowly injected until the neurosensory retina almost totally detached from the underlying retinal pigment epithelium.…”
Section: Establishment Of Retinal Detachmentmentioning
confidence: 99%
“…Earlier studies mainly focused on the mitochondrion-mediated pathway; the existence of mitochondrion-mediated pathway has been confirmed in the apoptosis of photoreceptors whereby the inhibition of key factors in above pathway prevented the photoreceptors from apoptosis. [8][9][10] However, the inhibitors can only partly rescue photoreceptors, suggesting the existence of other pathways for the apoptosis process after RD.…”
Section: Introductionmentioning
confidence: 99%
“…During death domain receptor-induced apoptosis, RIP1 is cleaved and inactivated by caspase-8, the process of which is prevented by caspase inhibition (13). It has been unclear how RIP1 kinase mediates programmed necrosis, but recent studies revealed that the expression of RIP3 and the RIP1-RIP3 binding through the RIP homotypic interaction motif is a prerequisite for RIP1 kinase activation, leading to reactive oxygen species (ROS) production and necrotic cell death (14-16).In a rodent model of retinal detachment, we have shown that TNF-α expression levels increase substantially (17) and that caspases are activated after retinal detachment (18,19). However, caspase inhibition by Z-VAD fails to prevent the retinal detachment-induced photoreceptor death (20).…”
mentioning
confidence: 99%
“…In a rodent model of retinal detachment, we have shown that TNF-α expression levels increase substantially (17) and that caspases are activated after retinal detachment (18,19). However, caspase inhibition by Z-VAD fails to prevent the retinal detachment-induced photoreceptor death (20).…”
mentioning
confidence: 99%
“…31,32 This study showed that exogenous EPO after RD significantly reduced the number of TUNEL-positive cells, indicating that EPO partially inhibited apoptosis. Caspase-3 is the final executor of apoptosis and is also involved in photoreceptor cell apoptosis after RD.…”
Section: Eyementioning
confidence: 70%